The human endometrium - histochemical and ultrastructural changes during normal menstrual cycle. - Takano Morón, Juan (2015)
The development of fixation techniques, embedding and sectioning of tissues for electronic microscopy made it possible, since the early 60s, valuable information on endometrial ultrastructure of various animal species and women to accumulate in normal and hormone activity. Anchor works and collaborators, Nilsson, of Clyman, Tarzakis and Cavazos et al highlight what limited as far as ultrastructural details of the endometrium of women during the normal menstrual cycle is concerned.